Abnormal Processing of the Glycoprotein IIb Transcript due to a Nonsense Mutation in Exon 17 Associated with Glanzmann’s Thrombasthenia - Tomiyama, Yoshiaki; Kashiwagi, Hirokazu; Kosugi, Satoru; Shiraga, Masamichi; Kanayama, Yoshio; Kurata, Yoshiyuki; Matsuzawa, Yuji (Thrombosis and Haemostasis, 1995)
We analyzed the molecular genetic defect responsible for type I Glanzmann’s thrombasthenia in a Japanese patient. In an immunoblot assay using polyclonal anti-GPIIb-IIIa antibodies, some GPIIIa (15% of normal amount) could be detected in the patient’s platelets, whereas GPIIb could not (<2% of normal amount). Nucleotide sequence analysis of platelet GPIIb mRNA-derived polymerase chain reaction (PCR) products revealed that patient’s GPIIb cDNA had a 75-bp deletion in the 3’ boundary of exon 17 resulting in an in-frame deletion of 25 amino acids. DNA analysis and family study revealed that the patient was a compound heterozygote of two GPIIb gene defects. One allele derived from her father was not expressed in platelets, and the other allele derived from her mother had a 9644C → T mutation which was located at the position -3 of the splice donor junction of exon 17 and resulted in a termination codon (TGA). Moreover, quantitative analysis demonstrated that the amount of the abnormal GPIIb transcript in the patient’s platelets was markedly reduced. Thus, the C → T mutation resulting in the abnormal splicing of GPIIb transcript and the reduction in its amount is responsible for Glanzmann’s thrombasthenia.